ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI TINGKAT KEPUASAN PELANGGAN PADA ROCK ROYAL CAFE DAN FAMILY KARAOKE NAMLEA - Muswan, La Ode; Leko, Legi (JIEM : Journal Of International Entrepreneurship And Management, 2024)
This study aims to analyze the factors that influence customer satisfaction at Rock Royal Cafe and Family Karaoke Namlea. The research adopts a quantitative approach with data collection through questionnaires distributed to customers who have visited these establishments. Data analysis is conducted using descriptive statistics and linear regression to determine the relationship between factors such as service quality, price, cleanliness, and facilities with customer satisfaction levels. The results indicate that these factors significantly affect customer satisfaction. Service quality and cleanliness are the most dominant factors in enhancing customer satisfaction at both establishments. This study is expected to provide recommendations for management to improve and enhance service quality and facilities in order to maintain customer satisfaction.